2007
DOI: 10.1159/000100834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Additional Sampling in the TRUS-Guided Biopsy for the Diagnosis of Prostate Cancer

Abstract: Aim: To evaluate the diagnostic value of 10+ systematic sampling technique when performing transrectal ultrasound-guided (TRUS) prostate biopsy, compared with the sextant biopsy technique for patients with suspected prostate cancer. Methods: 286 patients with suspected prostate cancer were included in the study. Patients were eligible for the study if they had serum levels of prostate-specific antigen (PSA) >4 ng/ml or ratio PSA <0.25 and/or an abnormal digital rectal examination (DRE). The population sample w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
23
0
1
Order By: Relevance
“…With regard to the number of prostate biopsy cores, we have performed systematic TRUS-guided prostate biopsy with 10 or more than 10 cores since 1999 to increase the detection rate of prostate cancer. Recently several authors confirmed that systematic TRUS-guided prostate biopsy with more than 10 cores improved the detection rate of prostate cancer compared to the sextant biopsy [7,8] . On the other hand, taking biopsy cores around the urethra increases the risk of hematuria complications, and Eskew et al [13] reported a result of almost no cancers in midline biopsies.…”
Section: Discussionmentioning
confidence: 96%
“…With regard to the number of prostate biopsy cores, we have performed systematic TRUS-guided prostate biopsy with 10 or more than 10 cores since 1999 to increase the detection rate of prostate cancer. Recently several authors confirmed that systematic TRUS-guided prostate biopsy with more than 10 cores improved the detection rate of prostate cancer compared to the sextant biopsy [7,8] . On the other hand, taking biopsy cores around the urethra increases the risk of hematuria complications, and Eskew et al [13] reported a result of almost no cancers in midline biopsies.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, as the number of biopsy specimens increases, discomfort tends to become severer. Although the optimum number of biopsy cores is still unknown, 10 and extended 10+ core prostate biopsy techniques are recommended at the present time [4] . Therefore, pain relief during prostate biopsy is an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing beyond sextant improves detection [6,14,18,19] and has become commonplace [20] , but the optimum number of biopsies is unknown. Since transition zone sampling has not been shown to significantly increase detection, in an attempt to define the utility of increasing number of biopsy cores, this study randomly assigned men at first biopsy to 12 or 15 cores without focusing on the transition zone.…”
Section: Discussionmentioning
confidence: 99%